The Effect of Gramoxone Application on Eupatorium odoratum - Nair, P. N. (Indian Forester, 1973)
The weed Eupatorium odoratum Is a menace in the plantations of Kerala. An experiment was designed and carried out to find the effectiveness of the weedicide Gramoxone on this weed at various concentrations ranging from 0.1% to 0.3% by single and repeated sprayings at three different times of the year at three different localities. In two localities the treatment plots were In the open and In the other locality they were under partial shadc. The results have shown that in the open DO lasting control of the weed could be achieved even with 0.3% concentration of the weedicide sprayed three times a year. The hardier woody portions of the weed remained alive after treatment and new sprouts appeared after some time. The general indications are that under partial shade some control of the weed can be obtained at concentrations of 15% and above. Here when the concentration Is low the number of applications should be three or even more. On the whole, control of Eupatorium by spraying with Gramoxone is not very effective or economical as compared to manual methods.